(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This research examines the role of color and colorism in sculpture and its evolution in visual art throughout history. The article analyzes the development of color in sculpture from ancient times to the present day. In ancient Greece and Rome, sculptures were adorned with vibrant colors, which played a crucial role in creating realism. Later, during the Renaissance, the use of color decreased, with artists focusing on emphasizing the natural forms of the sculpture. In the 20th century, color began to be used as an independent element, offering new expressive possibilities for sculptures. In contemporary art, color is no longer just a decorative tool but a key element for enhancing emotional expression and engaging with the viewer. Modern technologies, such as 3D printing and synthetic plastics, have allowed artists to create works that change with variations in light and perspective, creating new ways of perceiving art.